Private anarchy: impossible community and the outsider's monologue in German experimental fiction - Buchholz, Paul (Northwestern University Press, 2018)
Introduction -- Voices of the vacuum: monologue in Schopenhauer, Dostoevsky, and Nietzsche -- Unworldly anarchism: Gustav Landauer's nihilist community -- Society of nobodies: Franz Kafka and the communal vacuum -- Monologue overgrown: the language of hypertrophy in Thomas Bernhard's Leichtlebig -- Nobody's friends: outsider community in Wolfgang Hilbig's prose -- Conclusion